Well-prefaced turns in English conversation: A conversation analytic perspective - Heritage, John (Journal of pragmatics, 2015)
•Paper is based on a large corpus of ordinary conversation.•Paper gives the first quantitative treatment of the functions of well-prefacing.•Discriminates and evaluates three approaches to preference.•Offers a new ‘my side-my side’ function for well.•Offers an integrated family resemblance treatment of functions. This paper presents evidence that the discourse particle well functions as a generalized procedural alert that the turn it prefaces will privilege its speaker's perspectives, interests or project relative to the expectations for action established in the prior turn or sequence. Using data from a corpus of 748 well-prefaced turns, a range of contexts that enrich and specify this function are identified including (i) responses to questions, (ii) topic shift and topic closure, and (iii) ‘my side’ corroborations of descriptions and judgments.